Effect of boron on sunflower (Helianthus annuus) productivity and grain composition under sulphate dominated saline conditions - SINGH, KULDEEP; RAMPRAKASH, RAMPRAKASH; SANGWAN, ANURAG; YADAV, ARVIND; CHAUDHARY, KAUTILYA (The Indian Journal of Agricultural Sciences, 2020)
The present study was carried out at CCS Haryana Agricultural University, Hisar, India in 2015– 16 to examine the response of Boron applications to sunflower (Helianthus annuus L.) under sulphate dominated salinity with four salinity (EC) levels (Control, 4, 8 and 12 dS/m) and five Boron levels (Control, 1, 3, 6, 12 mg/kg). The per cent decrease in germination with increasing levels of salinity at high boron level was 1.87, 2.74 and 13.21, respectively, as compared to the control. The per cent reduction in seed yield of sunflower as compared to control was 7.35, 24.80 and 52.06% at salinity levels of 4, 8 and 12 dS/m at 12 mg/kg boron level, respectively. Similarly increase in Boron levels significantly reduced the seed yield of sunflower. Maximum oil content (40.93%) was observed in control while minimum oil content (34.40%) was observed at high salinity and boron level. Salinity stress at 12 dS/m reduced protein content 13.53% as compared to control conditions. Protein content was decreased significantly at 6 and 12 mg/kg. The salinity and boron have detrimental effects on germination, seed yield, protein content and oil content of sunflower. The concentration of ions (Ca2+, Na+, SO42- and C1-) in sunflower seed was higher in saline condition. Boron levels increased the concentration of Ca2+, Na+ and C1- in sunflower seed under sulphate dominated salinity which furthers reduced plant survival and negates the productivity.